Agro-based industry, mobile phone and youth: a recipe for success - Mohamed Shaffril, Hayrol Azril; Hassan, Md. Salleh; Abu Hassan, Musa; Alby, Jeffrey Lawrence D'Silva (EuroJournals Publishing, 2009)
Mobile phone has become more relevant in the modern days and agriculture is one of the sectors that benefited from it. Mobile phone without doubt is one of the main instruments that can help agriculture community especially to ease the communication process and agriculture community must be encouraged to utilize it wisely. This paper tends to know the perception of Malaysian youth agro-based entrepreneurs regarding the contribution of mobile phone in their agro-business. Results indicated that majority of respondents used mobile phone frequently while majority of the respondents had high perception on the contribution of mobile phone in their agro-business productivity. Results also indicated that majority of Malaysian agro-based entrepreneurs believed that mobile phone can help them in getting information on agriculture every time they need it. Pearson Correlation employed proved that age has negative and significant correlation with perception on mobile phone contribution.